RANCANG BANGUN WEBSITE KETERSEDIAAN OBAT UNTUK MENINGKATKAN AKSES DAN LAYANAN KESEHATAN - Amelia, Rizki; Mardiana, Ardi (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2025)
The healthcare industry requires an efficient drug inventory management system to improve service quality and patient access to medicines. This research aims to develop a web-based drug availability application using the Rapid Application Development (RAD) methodology. The system includes drug inventory management, patient data management, transaction recording (incoming and outgoing drugs), and automatic reporting features. This web-based application was developed using NextJS framework, JavaScript programming language, and MySQL database to provide a user-friendly interface for clinic staff. The development methodology follows the RAD approach which consists of requirements planning, user design, construction, and cutover phases. Black box testing results show that all system functions work properly with 100% success rate. The system successfully provides automated drug inventory management, transaction monitoring, and comprehensive reporting features that can improve operational efficiency at Guvili Clinic. This drug availability management system offers an effective solution to replace manual recording methods and provides real-time access to drug inventory data for better healthcare service management.